2018
DOI: 10.12688/f1000research.14143.1
|View full text |Cite
|
Sign up to set email alerts
|

A threshold model for receptor tyrosine kinase signaling specificity and cell fate determination

Abstract: Upon ligand engagement, the single-pass transmembrane receptor tyrosine kinases (RTKs) dimerize to transmit qualitatively and quantitatively different intracellular signals that alter the transcriptional landscape and thereby determine the cellular response. The molecular mechanisms underlying these fundamental events are not well understood. Considering recent insights into the structural biology of fibroblast growth factor signaling, we propose a threshold model for RTK signaling specificity in which quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 89 publications
(88 reference statements)
1
76
0
Order By: Relevance
“…These data suggest that non-detectable short-lived IL-6/gp130 complexes can partially engage signaling, but fail to trigger a full response, evoking a kinetic-proof reading model. A kinetic-proof reading model has been previously proposed for other ligand-receptor systems, including the T cell receptor system (TCR) (McKeithan, 1995) and more recently Receptor Tyrosine Kinases (RTKs) (Zinkle and Mohammadi, 2018). In these two systems, changes on ligand-receptor complex half-life induce phosphorylation of different Tyr pools in the receptors ICDs, ultimately recruiting and activating different signaling effectors (Acuto et al, 2008;Lemmon and Schlessinger, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that non-detectable short-lived IL-6/gp130 complexes can partially engage signaling, but fail to trigger a full response, evoking a kinetic-proof reading model. A kinetic-proof reading model has been previously proposed for other ligand-receptor systems, including the T cell receptor system (TCR) (McKeithan, 1995) and more recently Receptor Tyrosine Kinases (RTKs) (Zinkle and Mohammadi, 2018). In these two systems, changes on ligand-receptor complex half-life induce phosphorylation of different Tyr pools in the receptors ICDs, ultimately recruiting and activating different signaling effectors (Acuto et al, 2008;Lemmon and Schlessinger, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, the biophysical consequences for the downstream pathways and cell behavior modes remain unclear. Previous work has revealed that the dose and the geometry of the ligands, the distinct receptor expression profiles on cell surfaces, the time‐dependent effects and frequency of ligand–receptor interaction, and receptor oligomerization status act in concert to perform complex signal processing for different cell fates . In the bone morphogenetic protein (BMP) signaling pathway, for example, more than 30 different ligands interact with only seven different receptors.…”
Section: Natural Regulatory Mechanisms Of Cellsurface Receptorsmentioning
confidence: 99%
“…However,t he biophysicalc onsequencesf or the downstream pathways and cell behavior modesr emain unclear.P revious work has revealed that the dose and the geometry of the ligands, the distinct receptor expression profileso nc ell surfaces, the time-dependent effects and frequency of ligand-receptor interaction, and receptor oligomerization statusa ct in concert to perform complex signal processing for different cell fates. [2,7] In the bone morphogenetic protein (BMP) signaling pathway,f or example, more than 30 different ligands interact with only seven different receptors. When exposed to combinations of different BMP ligands, cells use their repertoire of BMP receptorst op erceive mixed ligand milieus and to orchestrate both homodimerization and heterodimerization of different receptors, with conversion into specific signaling output patterns, leadingt od istinct cell fate decisions.…”
Section: Natural Regulatory Mechanisms Of Cell-surface Receptorsmentioning
confidence: 99%
See 2 more Smart Citations